Impact of institutional organization on research productivity and multidisciplinarity - García-Rodríguez, Alberto; Barrio, R. A.; Govezensky, Tzipe; Tagüeña, Julia; Pérez, Miguel Robles; Calvet, Humberto Carrillo; Jiménez Andrade, José Luis; Arencibia-Jorge, Ricardo; Kaski, Kimmo (Frontiers in Physics, 2023)
In this article we will describe a model to examine the influence of differently organized institutions on their scientific productivity. We take two extreme cases, on one hand an institution divide in departments with no collaboration between people in different departments. These could be disciplines or merely projects. As on the other extremes we consider an institution that allows interactions between all individuals, without a departmental structure. We compare the results with data of an institution which has changed its organization and policies during the last 30 years.